2017
DOI: 10.1111/jcmm.13328
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 contributes to persistent autophagy and heart failure in mice after myocardial infarction

Abstract: Toll‐like receptors (TLRs) are essential immunoreceptors involved in host defence against invading microbes. Recent studies indicate that certain TLRs activate immunological autophagy to eliminate microbes. It remains unknown whether TLRs regulate autophagy to play a role in the heart. This study examined this question. The activation of TLR3 in cultured cardiomyocytes was observed to increase protein levels of autophagic components, including LC3‐II, a specific marker for autophagy induction, and p62/SQSTM1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 55 publications
3
33
0
Order By: Relevance
“…Fallach et al reported increased immunohistochemical staining for TLR4 in ischaemic mouse heart. Our published data showed increases in mRNAs and proteins for TLR2, TLR3 and TLR4 in cultured cardiomyocytes exposed to ischaemia, as well as heart tissue subjected to ischaemia . As a fact, we have examined more members of TLR family and have obtained data, which are presented herein, showing universal increases in Tlr mRNAs in ischaemic cardiomyocytes and myocardium.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Fallach et al reported increased immunohistochemical staining for TLR4 in ischaemic mouse heart. Our published data showed increases in mRNAs and proteins for TLR2, TLR3 and TLR4 in cultured cardiomyocytes exposed to ischaemia, as well as heart tissue subjected to ischaemia . As a fact, we have examined more members of TLR family and have obtained data, which are presented herein, showing universal increases in Tlr mRNAs in ischaemic cardiomyocytes and myocardium.…”
Section: Introductionmentioning
confidence: 60%
“…Our published data showed increases in mRNAs and proteins for TLR2, TLR3 and TLR4 in cultured cardiomyocytes exposed to ischaemia, as well as heart tissue subjected to ischaemia. [7][8][9] As a fact, we have examined more members of TLR family and have obtained data, which are presented herein, showing universal increases in Tlr mRNAs in ischaemic cardiomyocytes and myocardium. To uncover the underlying mechanism stimulating Tlr expression in cardiomyocytes, the present study screened transcription factors (TFs) that potentially regulate TLR gene transcription, and identified forkhead box C1 (FOXC1) as an ischaemia-responsive TF that up-regulates the expression of TLR members in myocardial ischaemia.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Tlr3 ‐deficient mice also exhibited more severe pulmonary hypertension following exposure to chronic hypoxia (13). However, TLR3 represents an injurious factor during I/R injury (14) and myocardial infarction (15). And it also plays a deleterious role in mediating cardiac dysfunction in sepsis (16).…”
mentioning
confidence: 99%